Razširjenost neželenih učinkov med recepta prostimi zdravili in zdravili na recept v občini Slovenska Bistrica - Golub, Jana (Zdravstveno varstvo, 2007)
Background: There is a paucity of data on the usage of medicinal herbs for self healing in Slovenia. Among various health problems that doctors encounter in their everyday practice, some may be due to untoward side-effectsfrom prescription drugs or from medicines taken for self healing. The objective of the paper was to investigate this issue in the Slovenska Bistrica community. Patients and methods: The survey questionnaire was distributed to a random sample of population registered with GP offices in theSlovenska Bistrica municipality. Our aim was to determine the rate of herbal and other synthetic medicines being used by the population for self healing, and to determine possible side-effects occurring as a result of combining the former medication with drugs prescribed by the doctor. Results: The survey included a random sample of 597 patients of both sexes and different ages. Only two questionnaires were excluded as being invalid. Some of the individuals participating in the survey were completely healthy and some received treatment for one or several illnesses. Healthy subjects and patients with chronic diseases took prescribed drugs, as well as herbal preparations and other synthetic over-the-counter drugs for both curative andpreventive purposes. Garlic, St. John's wort, gingko, hawthorn, ginseng, valerian and grapefruit juice were the most commonly used herbs. The frequencyof side-effects reported by patients taking herbal preparations was compared with that reported by individuals using synthetic medicines along with other prescribed drugs. Conclusion: Combining synthetic or herbal preparations for self-healing with prescription medicines was found to increase the incidence of undesirable side-effects. To facilitate and shorten the diagnostic work in patients experiencing side-effects, it is essential to be familiar with possible interactions between various medicines and to know the patient's habits, as well as to actively inquire as to whether he/she usesprescribed drugs together with other preparations or herbs.
Keywords: drug; neželeni učinki; samozdravljenje; therapy; zdravila; zdravilne rastline; zdravljenje